Multimode optical fiber strain monitoring for smart infrastructures - Ahmed Hisham E. Morshed; Raghied M. Atta (Ain Shams Engineering Journal, 2023)
The in-service monitoring of civil infrastructures is an important task required to achieve their smart operation. This task requires the installation of sensors to continuously check and control the structures’ status in order to fulfil the demanded operating conditions and avoid the occurrence of malfunctions. This work presents an investigation of the use of multimode optical fiber sensors in detecting strain and vibration of infrastructures. The multimode fiber sensor is composed of a single mode – multimode – single mode concatenated fiber structure. To explore its practical application for strain monitoring, the sensor is used to measure the strain on a pressurized pipe and its performance compared with the well-developed fiber Bragg grating sensor. The detuning of spectral features of the multimode sensor transmission with increasing pipe pressure is found to have a good linearity (R2 ∼ 0.95) and is more sensitive to strain compared to that of the fiber Bragg grating.